A COMPARATIVE STUDY FOR THE QUANTITATIVE DETERMINATION OF DIFFERENT BRANDS OF PARACETAMOL TABLET USING UV-VISIBLE SPECTROPHOTOMETRIC, POTENTIOMETRIC AND TRIMETRIC METHODS. - Tilki, Dr. Tamiru; Singh, Prof (Dr.) Vijender; Arya, Hema (Journal of Biomedical and Pharmaceutical Research, 2019)
Paracetamol (acetaminophen) is a widely used over-the-counter analgesic, antipyretic and a mild anti inflammatory drug. In several developing countries some of pharmaceutical industries sale fake, counterfeit and substandard drugs which affect the health of people. The present study investigates the comparison for the quantitative determination of various brands of paracetamol tablet using UV-Visible spectrophotometric, potentiometric and trimetric methods. Four brands (Pacimol, Paracip, Parazest, and Crocin) of paracetamol tablets having 500 mg strength were purchased from various pharmacy shops within Pari chowk and Jagat market in Greater Noida, India. Weight variation test was performed before the assay of paracetamol samples. The result of tablets weight variation (Mean ± S.D) of Crocin, Parazest, Paracip and Pacimol brand was 0.66 ± 0.014, 0.64 ± 0.010, 0.58 ± 0.007 and 0.55 ± 0.009 respectively. All brands showed different mean weight which indicates the use of different excipients in the different brands. The ranges of the amount of paracetamol content (g/tab) for paracetamol samples analyzed using UV-Visible spectrophotometric, potentiometric and trimetric methods were from 0.49195-0.52010, 0.48300-0.52100 and 0.48106-0.50110 respectively. The results indicated that all four brands of paracetamol tablets have sufficient quantity and amount is approximately similar to the company’s recommended or claimed value. Similarly, the ranges of percentage content (assay) of the analyzed samples using UV-Visible spectrophotometric, potentiometric and trimetric methods were from 98.69-104.20%, 96.60-104.20%, and 96.21-100.22% respectively. The assay results indicated that variation among all brands and this may show that different manufacturer formulates the different brands are under the IP specification. However, all of the brands of the tablets under the study were complied with the IP specification and passed for weight variation test and assay conducted on it. Hence, the drug control authority of the government should be continuously monitored the safety, quality, and efficacy of paracetamol tablet through post marketing surveillance practices, and the proper internal quality control of the pharmaceutical companies need to take further necessary steps to ensure the continuity in the establishment of the product quantity and quality. Keywords: Assay, Brands, Comparative, Determination, Paracetamol, Tablets